2005
DOI: 10.1902/jop.2005.76.8.1275
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between the Effects of Photodynamic Therapy and Conventional Therapy on Microbial Reduction in Ligature‐Induced Peri‐Implantitis in Dogs

Abstract: These findings suggest that photodynamic therapy is a non-invasive method that could be used to reduce microorganisms in peri-implantitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0
34

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(180 citation statements)
references
References 30 publications
3
143
0
34
Order By: Relevance
“…It has been established that PS which possess a pronounced cationic charge can rapidly bind and penetrate bacterial cells and therefore these compounds demonstrate a high degree of selectivity for killing microorganisms compared to host mammalian cells [23,24]. PDT has been studied as a promising approach to eradicate oral pathogenic bacteria [25,26] that cause endodontic diseases [27][28][29], periodontitis [30], peri-implantitis [31] and caries [32]. Some PS, such as toluidine blue and methylene blue have been tested in association with low-intensity red lasers to promote bactericidal effects in vivo [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that PS which possess a pronounced cationic charge can rapidly bind and penetrate bacterial cells and therefore these compounds demonstrate a high degree of selectivity for killing microorganisms compared to host mammalian cells [23,24]. PDT has been studied as a promising approach to eradicate oral pathogenic bacteria [25,26] that cause endodontic diseases [27][28][29], periodontitis [30], peri-implantitis [31] and caries [32]. Some PS, such as toluidine blue and methylene blue have been tested in association with low-intensity red lasers to promote bactericidal effects in vivo [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Although published data on PDT for oral pathogens are comparably limited and most of the studies had been performed in vitro, it had been proposed that PDT either alone or in combination with other strategies may be a useful option to treat pathogens involved in periodontitis [7], peri-implantitis [8], endodontitis [9] and caries [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the high bactericidal effect of photodynamic therapy and that it may be a valuable alternative to conventional mechanical approaches (88,89,90). Microbiological reduction was observed in vivo following photodynamic therapy in the treatment of peri-implantitis in dogs (91,92). Also, it was reported in an animal model that photodynamic therapy can reduce periodontal disease progression and periodontal tissue destruction in experimentally induced periodontal disease (93) Therefore, the potential effects of photodynamic therapy should be studied more extensively to establish the optimal conditions during clinical application.…”
Section: Other Usesmentioning
confidence: 99%